Sodobnost Keynesove misli o finančnih trgih - Dajčman, Silvo (Naše gospodarstvo, 2006)
Modern financial markets are characterized by excess financial price and return volatility, rising volume of financial transactions, clusters of volatility and long memory in financial time series. All these features are a step away from the prevailing doctrine of financial markets as represented by the efficient financial markets hypothesis. Keynes theory of financial markets offers an alternative explanation of financial markets: financial markets in Keynes theory are nonergodic, and economic decisions are influenced by sociological and psychological factors. This article analyzes Keynes influence on contemporary financial markets theory and empirical research.
Keywords: finančni trg; keynesianizem; postkeynesianizem; trg kapitala; ekonomske teorije; neoklasična ekonomska teorija